Electrochemical Enhancement of Nickel oxide Dispersed Graphene Sheets as Electrode Material for Energy Storage Application. (2018) - Siddeswara, D.M.K; Mahesh, K.R.Vishnu; Mylarappa, M.; Nagaswarupa, H.P.; Shravana Kumara, K.N; Raghavendra, N.; Prashanth, S.C.
Abstract: In present work, graphene was doped with nickel oxide to improve theperformance of electrochemical applications. Initially reduced graphene oxide (rGO) was synthesised by modified Hummer's method by using Graphite as a precursor material, as synthesised rGO is used to prepare rGO/NiO nanocomposite in one step. Then the synthesised GO and rGO/NiO materials are subjected to different characterisation for rectification of the compounds. The synthesised GO and rGO/NiO compositewere characterised by using X-ray Diffracto meter (XRD) and Surface morphology examined by using Scanning Electron Microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) for functional group attachments. Graphite, rGO and rGO/NiO nanocomposites were investigated through cyclic voltammetry and electrochemical impedance spectroscopy.From, it is clear that the charge transfer resistance is low in the electrode with rGO/NiO followed by a rise in the capacitance of the electrode. From the obtained results it is confirmed that the electrochemical behaviour of rGO/NiO composites materials was superior as compared to graphite and rGO.